Prototype of AC Microgrid Solar Power Plant with Off-Grid System - Marhatang, Marhatang; Yunus, A.M Shiddiq; Djalal, Muhammad Ruswandi; Alkautsar, Rifaldi; Caturindah, Winarty (Politeknik Negeri Ujung Pandang, 2023)
AC microgrid solar power plants can be used as an alternative to overcome the problem of unevenly distributed electricity demand in Indonesia. Prior to implementation, a model or prototype is required to test and provide insights about the solar power plant's functionality as an electric energy generator. The aim of this research was to develop a solar power plant for AC loads and assess the performance of AC Microgrid solar power plants using an Off-grid system. The test results lead to the conclusion that the efficiency of the AC Microgrid solar power plant with the Off-grid system is highly dependent on the intensity of solar radiation, whether it is high or low, striking the panel. The solar panel efficiency ranged from a maximum of 5.54% to a minimum of 4.16%, while the system efficiency varied between a maximum of 8.65% and a minimum of 7.95%.